2021
DOI: 10.9734/arrb/2021/v36i730398
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Cultivation Technology Package on Tidal Swamp Lands in Indonesia

Abstract: The main constraints of the tidal swamp lands in Indonesia for soybean growth are low soil pH, high Al saturation, and low nutrient availability of N, P, K, Ca, and Mg. The objectives of this research were to determine tolerance of several soybean varieties to Al saturation level, and to obtain a technological package for soybean cultivation which was suitable for farmers to adopt on tidal swamp lands. The research consisted of two stages of study. The first stage formulated of technology package, and the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Until 2021, in Indonesia, there are only four soybean varieties released having good adaptation for tidal swamp lands, namely Menyapa, Lawit, Depas1, and Depas2 [10]. However, Harsono et al [11] reported that Anjasmoro, Panderman, Dega1, and Demas varieties could also grow well at 20-30% of soil Al-CEC saturation on tidal swamps (Table 3). Note : dw = Dry weight…”
Section: Adaptive Varietiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Until 2021, in Indonesia, there are only four soybean varieties released having good adaptation for tidal swamp lands, namely Menyapa, Lawit, Depas1, and Depas2 [10]. However, Harsono et al [11] reported that Anjasmoro, Panderman, Dega1, and Demas varieties could also grow well at 20-30% of soil Al-CEC saturation on tidal swamps (Table 3). Note : dw = Dry weight…”
Section: Adaptive Varietiesmentioning
confidence: 99%
“…When oxidation occurs, pyrite compounds in the soil on tidal swamp lands will produce sulfuric acid, causing a great acidification process. This condition is less favorable for soybean production because the crops are generally only adaptive to soils with a pH of around five and an Al-CEC saturation of 20-30% [11]. Soil water management can be applied to reduce the pyrite content as the soil is in a reductive condition [12].…”
Section: Water Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Harsono [26] reported that the high Al saturation and nutrient problems in soybean plants on tidal swamps in South Kalimantan can be corrected by using dolomite until the Al-dd saturation decreases to around 30% by using organic fertilizers 1.25 t/ha, bio-fertilizer Agrisoy 0.25 kg/50 kg seeds, Urea 50 kg/ha, SP36 75 kg/ha and 50 kg KCl/ha. With this fertilization package, soybean yields on tidal swamps in South Kalimantan can reach 2.0 t/ha.…”
Section: Improvement Of Soil Chemical Properties For Soybean On Tidal Landsmentioning
confidence: 99%